Interferon-free treatment choice according to baseline RASs leads to high SVR rates in HCV genotype 1 infected patients. Issue 7 (July 2018) - Peiffer, Kai-Henrik; Vermehren, Johannes; Kuhnhenn, Lisa; Susser, Simone; Dietz, Julia; Finkelmeier, Fabian; Weiler, Nina; Welzel, Tania; Grammatikos, Georgios; Zeuzem, Stefan; Sarrazin, Christoph
Abstract: Aim: Different combinations of direct antiviral agents (DAA) lead to high SVR rates in HCV genotype 1 infected patients. However, presence of baseline resistance-associated substitutions (RASs) represents a major risk factor for treatment failure. It is unknown whether choice of treatment based on RASs has the potential to decrease virologic failure rates. Methods: Population-based sequencing of NS3 and NS5A genes was performed in HCV genotype 1 infected patients at a German university hospital. Treatment was individually selected based on resistance analyses. Results: In total, 319 patients (50% treatment-experienced and 30% with cirrhosis) were included. With the treatment choice based on the baseline NS3 and NS5A resistance profile SVR rates between 96 and 100% were observed in all subgroups, including treatment-experienced patients with cirrhosis and HCV genotype 1a infected cirrhotic patients. Conclusions: The choice of treatment based on the RASs status at baseline may be beneficial for optimizing treatment efficacy in patients with HCV genotype 1 infection and risk factors for treatment failure.